PERSEPSI MANAJER BANK SYARI'AH DI JAWA TIMUR TERHADAP PRAKTEK MANAJEMEN LABA: SUATU TINJAUAN ATAS PERSPEKTIF ETIKA (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2009)
The purpose of this research is to analyse the perception of Bank Syariah's Managers of East Java regarding earnings management practices. Ethical perspective observation concerned with type or method of earnings management, consistency of Generally Accepted accounting Principles, direction of earnings management, materiality of earnings management, period of impact, and objective of earnings management. Population of this research were managers who involved in Syariah Banking fields and located in East Java Province. Base on data from Bank Indonesia, 23 bank syariah operate their business at East Java Province. Base on the unequal-test taken for, the conclusion are; (I) there is significant ethical perspective regarding earnings management practices, which concerned with consistency with generally accepted accounting principles, and company's long term privileges or individual privileges; (2) there are significant difference of ethic perspective regarding earnings management practices which concern with usage of accounting methods or operational methods, Direction of earnings management are by increase or reduce earnings, manipulate of profit in material or non-material amount, and execute at the end of year or end of quarterly.